The Implementation of Street Children Development Policy in the West Jakarta Social Sub-Agency - Sari, Mira Permata (Lembaga Penerbitan Universitas Esa Unggul, 2021)
Street children in Jakarta City have been increasing every year and their lifestyle tends to be desperate. The following are the problems faced by street children: school dropouts, intimidations, drugs and addictive substances abuses, susceptible to diseases, shack dwellings in slum environments, risk of being hit, a gap in the family relationship. The research question is: How is the lmplementation of Street Children Development Policy in Social Branch Office of West Jakarta. This study used descriptive qualitative approach. The objective of descriptive qualitative research describes facts, objects, or subjects as they are with the aim of systematically describing the facts and characteristics of the object under study accurately. Data collection is conducted using interview, observation and documentation techniques. The result of the study showed that the lmplementation of Street Children Development Policy in Social Branch Office of West Jakarta has run well, Social Branch Office of West Jakafta already has several Children's Social lnstitutions, one of which is Children's Social lnstitutions 4 Cengkareng, and there is also an NGO (Non-governmental organization) Uswatun hasanah in West Jakarta. Even though the Social Branch Office of West Jakarta has implemented the street children development well, there are still obstacles in fostering street children who come from street children, families of street children, and the lack of public information on dealing with street children. Social Branch Office of West Jakarta has an effort to overcome these obstacles, by collaborating with the Civil Service Police Unit of lndonesia and the Police to control and supervise street children, the children's social institutions participate in supervising the development of street children, P3S officers (social control service officers) of the Social Branch Office of West Jakarta reaches back to the street children and will be handed back to the orphanage for their guidance, Social Branch Office of West Jakarta collaborates with the Children's Social lnstitution for the social rehabilitation of street children